Perlindungan Anak Buruh Migran di Kabupaten Cirebon (Analisis Terhadap Konsep Dampak Anak yang Ditinggalkan) - Suryadi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2017)
Migration is a natural process of human population dynamics that move from place to place for a wide variety of orientations. The phenomenon of international migration is often an overview of the economic situation of a country in equality. Child is the mandate of Almighty God, in their houlders the future of the family, the nation and the state will be handled. Therefore the completion of their optimal growth and development is the duty of the parents and all community elements, including the state to participate in its favor. Child Rights and Protection Act (UUPA) is a manifestation of the seriousness of the state in implementatng the ringhts of the children while protecting them from potential violence that is always threatening. The phenomenon of migrant workers makes children face problem by lack of primary escort their growth process, especially the mother. The role of the father or mother became the sole companion of children and family members assisted potentially unable to meet the data protection and rights of children. Based on the survey results in general the proportion of the fulfillment of 4 (four) childrenâ€™s fundamental rights, namely the right to life, growng rights, protection rights and the rights of the opinion can be met by one if his parents or both become migrant workers. In the midst of the stuggle to fulfillment of social and economic needs by migrant workers, beside economic pressures and the exsistence of self in community life, international migration is a quick way to meet all needs, most sources person said needs serious attention to the problems of migrant workers children, by optimizing the existence of regulation with the synegy and policies and programs by both government and non-government organizations and community.Â Keyword: migrant workers, the rights and protection of children.Â